Evaluasi Program Asistensi Sosial Penyandang Disabilitas Berat - Sukmana, Djulaiha; Mahasiswa Program Megister Ilmu Kesejahteraan Sosial, FISIP Universitas Padjajaran, (UI Scholars Hub, 2022)
This study aims to determine the extent of the implementation of the Social Assistance Program for Persons with Disabilities (ASPD) and the impact on the fulfillment of basic needs. Individuals with severe disabilities cannot be rehabilitated and are unable to carry out daily activities such as eating, drinking, and bathing, therefore need the help of others. They are unable and do not have a steady source of income either from themselves or from others to meet basic needs. Families are their life foundation because they are unable to access key services such as health care programs and food distribution, due to their disability. Government assistance is expected to reduce the burden on families to care for members with disabilities. This research was conducted with a qualitative approach and a qualitative method. The data collection technique used is observation and interviews with beneficiaries. Research results from social assistance programs for people with severe disabilities have an impact on meeting the basic needs of people with severe disabilities. In the implementation program, Social Assistance for Persons with Severe Disabilities can be said to be insufficient to meet the basic needs of the community because the amount of funds provided is insufficient to meet the daily needs of the beneficiaries. In the implementation of the provision of funds is often too late. However, it can be said that the assistance has not been fully effective, but has had a positive impact on the beneficiaries considering that the beneficiaries of this program have made changes for the better, which are marked by fulfilling food needs, adding nutrition, and improving health.